Revisiting ‘Against Interpretation’: Reading ‘The Lunchbox’ as a Crisis in Art Criticism: Exploring the Ambiguity and Beauty of 'The Lunchbox' as a Case Study in Art Criticism (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper attempts to read, explain and justify the suitability of reading Sontag’s 1961 essay ‘Against Interpretation’ using a Bollywood movie The Lunchbox as a case in point. The reason for studying this movie is, even though it has an ambiguous ending, but the beauty portrayed on screen was enrapturing and enthralling. My paper does not attempt to praise or criticize the film but to celebrate the enrapturing and enthralling beauty it portrayed on screen. Should we watch films, as Sontag suggests, or should we interpret them? There is no need for politics in these pictures, no need for conceptual drag cloaking the images. The movie is an art, art about a life in art. Art has an aesthetic purpose more than utilitarian.